DTV-T2 coverage: comparison of measured and predicated signals - Bhashyakarla, Divya (2015)
Digital Video Broadcasting-Terrestrial Second Generation (DVB-T2) is currently the most up-to-date and advanced standard for Digital Television Broadcast. This standard was built on from its predecessor, the Digital Video Broadcasting-Terrestrial (DVB-T). Compared to DVB-T, the latest DVB-T2 standard offers several advantages in terms of spectrum efficiency, robustness, flexibility etc. Particularly in the case of Singapore, MediaCorp has been broadcasting its 7 free to air channels under the DVB-T2 format since 2013. However, although both the DVB-T and Analogue TV signals are also still being transmitted, it is expected that Singapore would fully switch over to DVB-T2 completely in the next few years. As such, the purpose of the Final Year Project was to measure the various parameters of the transmitted DVB-T/T2 signals such as Power, Carrier to Noise Ratio (C/N) etc. in different locations within Singapore. Apart from measuring, the results obtained were also analyzed to better understand the factors that can affect the TV signal reception. To attain these objectives, field meters such as the PROMAX TV Explorer HD+ and PROMAX HD Ranger+ were used along with antennas. Based on all the experiments that were conducted in the project, it can be concluded the TV signal reception is largely dependent on the obstructions around a test point for example. Obstacles such as trees and buildings can affect the Line of Sight from the transmitter to the receiver and can either block or reflect TV signals away. As such, the receiving antenna picks up many of these reflected signals which can either destructively degrade or constructively improve the signal power depending on their phase.